The Implementation of Bill 212 in Ontario Schools: Implications for Black Students - Gateri, Hellen; Richards, Donna (INYI Journal, 2021)
In February 2008, Bill 212 (Progressive Discipline and School Safety) replaced Bill 81, the Safe Schools Act of June 2000 with regards to the behaviour, discipline, and safety of students. However, since Bill 212 has been in effect, suspensions and expulsions have been unfairly implemented against Black secondary students. Using anti-Black racism (ABR) framework, this commentary paper explores the effects of sections 306–311 of the Bill on Black students within Ontario’s secondary school system. Based on this exploration, we will critically examine the way suspensions and expulsions have been employed through Bill 212 and the consequences of these disciplinary measures for Black students. We recommend alternative practices such as restorative justice and the integration of ABR framework to address students’ inappropriate behaviours in the educational system.